Neutralizing the Th1 effector cytokines, IFN-γ and TNF-α, attenuates established experimental autoimmune anti-myeloperoxidase glomerulonephritis - Nagai, Kei; Koo Yuk Cheong, Daniel; Cao Le, Anne; Tan, Diana Shu Yee; Ooi, Joshua Daniel; Gan, Poh-Yi (Frontiers in Immunology, 2025)
IntroductionThis study investigates the therapeutic potential of blocking key CD4+ Th1 effector cytokines, TNF-α and IFN-γ, in experimental anti-myeloperoxidase (MPO) glomerulonephritis (GN). The immunopathogenesis of MPO autoimmunity is biphasic, with an initial transient Th17 dominance followed by a sustained Th1 response, posing challenges for effective cytokine blockade.MethodsTo evaluate anti-cytokine therapy at distinct disease phases, we induced anti-MPO autoimmunity in mice through MPO immunization and triggered GN using anti-glomerular basement membrane (GBM) globulin at early (day 20) and late (days 32 and 38) stages. Mice received anti-TNF-α or anti-IFN-γ beginning 4 hours post-GN induction, with kidney injury assessed 4 or 10 days later.ResultsIn early anti-MPO GN (day 20), neither anti-TNF-α nor anti-IFN-γ mitigated kidney injury, consistent with Th17-driven autoimmunity at this stage. However, in late, established GN (day 32), TNF-α blockade significantly attenuated kidney injury, indicating its pathogenic role in Th1-driven disease. At day 32, IFN-γ neutralization induced a Th2 phenotypic shift, increasing IL-4 production in ex vivo MPO-stimulated lymph node cells and upregulating alternatively activated M2 macrophages. Despite this immunological shift, short-term IFN-γ blockade failed to confer renal protection. To assess whether prolonged IFN-γ neutralization is beneficial, we extended the induced kidney injury phase to day 38. In this setting, extending anti-IFN-γ treatment effectively attenuated kidney injury, highlighting its therapeutic potential in late-stage disease.ConclusionThese findings highlight the dynamic role of Th1 cytokines in anti-MPO GN, with TNF-α blockade benefiting established disease, while IFN-γ neutralization requires prolonged intervention. This study informs Th1-targeted strategies in MPO anti-neutrophil cytoplasmic antibody (ANCA)-associated GN.